You are on page 1of 14

SUMS OF ARCTANGENTS AND SOME FORMULAE OF

RAMANUJAN
GEORGE BOROS AND VICTOR H. MOLL

Abstract. We present diverse methods to evaluate arctangent and related


sums.

1. Introduction
The evaluation of arctangent sums of the form
(1.1)

tan1 h(k)

k=1

for a rational function h reappear in the literature from time to time. For instance
the evaluation of

X
2
3
(1.2)
tan1 2 =
k
4
k=1

is completely elementary and was proposed by J. Anglesio [1] in 1993. This is a


classical problem that appears in [7, 9, 13], among other places. The evaluation of

X
1 1
1 tan(/ 2) tanh(/ 2)

tan
(1.3)
= tan
k2
tan(/ 2) + tanh(/ 2)
k=1
is somewhat less elementary. R.J. Chapman [6] proposed in 1990 to evaluate this
sum in closed form (in terms of a finite number of trigonometric and hyperbolic
functions). This was solved by A. Sarkar [15] using the techniques described in
Section 3.
The goal of this paper is to discuss the evaluation of these sums and the related
rational sums
n
X
(1.4)
S(n) =
R(k)
k=1

for a rational function R. Note that tan

x will always denote the principal value.

We make use of the addition formula for tan1 x:


(
x+y
tan1 1xy
1
1
(1.5)
tan x + tan y =
x+y
tan1 1xy
+ sign x
Date: March 23, 2001.
1991 Mathematics Subject Classification. Primary 33.
Key words and phrases. Arctangent, Series.
1

if xy < 1
if xy > 1

GEORGE BOROS AND VICTOR H. MOLL

and
tan1 x + tan1

(1.6)

1
x

sign x.
2

2. The method of telescoping


The closed-form evaluation of a finite sum
n
X
S(n) :=
ak
k=1

is elementary if one can find a sequence {bk } such that


ak

= bk bk1 .

In this situation, the sum S(n) telescopes, i.e.


S(n) :=

n
X

ak =

k=1

n
X

bk bk1 = bn b0 .

k=1

This method can be extended to situations in which the telescoping nature of ak is


hidden by a function.
Theorem 2.1. Let f (x) be of fixed sign and define h by
h(x)

(2.1)

f (x + 1) f (x)
.
1 + f (x + 1)f (x)

Then
n
X

(2.2)

tan1 h(k) =

tan1 f (n + 1) tan1 f (1).

k=1

In particular, if f has a limit at (including the possibility of f () = ), then

(2.3)

tan1 h(k) =

tan1 f () tan1 f (1).

k=1

Proof. Since
tan1 h(k)

= tan1 f (k + 1) tan1 f (k),

(2.2) follows by telescoping.


Note. The hypothesis on the sign of f is included in order to avoid the case xy > 1
in (1.5). In general, (2.2) has to be replaced by
(2.4)

n
X

k=1

tan1 h(k)

tan1 f (n) tan1 f (1) +

sign f (k),

where the sum is taken over all k between 1 and n for which f (k)f (k + 1) < 1.
Thus (2.2) is always correct up to an integral multiple of . The restrictions on
the parameters in the examples described in this paper have the intent of keeping
f (k), k N of fixed sign.
Example 2.1. Let f (x) = ax + b, where a, b are such that f (x) 0 for x 1.
Then
a
h(x) =
(2.5)
a2 x2 + a(a + 2b)x + (1 + ab + b2 )

and (2.3) yields


(2.6)

tan1

k=1

a
a2 k 2 + a(a + 2b)k + (1 + ab + b2 )

tan1 (a + b).
2

Special cases: a = 1 and b = 0 give f (x) = x and h(x) = 1/(x2 + x + 1), and the
sum is

1
(2.7)
=
.
tan1 2
k +k+1
4
k=1

a = 2 and b = 0 give f (x) = 2x and h(x) = 2/(2x + 1)2 , so that

(2.8)

tan1

k=0

2
(2k + 1)2

.
2

Differentiating (2.6) with respect to a yields

X
pa,b (k)

(2.9)

k=1

qa,b (k)

1
,
1 + (a + b)2

where
= a2 k 2 + a2 k (1 + b2 )

pa,b (k)
and
qa,b (k)

= a4 k 4 + 2a3 (a + 2b)k 3 + a2 (2 + a2 + 6ab + 6b2 )k 2 +


2a(a + 2b)(1 + ab + b2 )k + (1 + b2 )(1 + a2 + 2ab + b2 ).

Special cases: a = 1 and b = 0 give

X
k2 + k 1
4
k + 2k 3 + 3k 2 + 2k + 2

k=1

1
.
2

a = 1/2 and b = 1/3 give

k=1

81k 4

9k 2 + 9k 40
+ 1269k 2 + 1932k + 2440

378k 3

1
.
61

Let a = 2b and differentiate with respect to b to produce

X
4b2 k 2 (1 + b2 )
1
=
.
16b4 k 4 + 8b2 (1 b2 )k 2 + (1 + b2 )2
2(1 + b2 )
k=1

Mathematica evaluates this last sum.


Example 2.2. This example considers the quadratic function f (x) = ax2 + bx + c
under the assumption that f (k), k N has fixed sign. For instance this happens if
b2 4ac 0. Define
1 + ac + bc + c2
ab + b2 + 2ac + 2bc
a2 + 3ab + b2 + 2ac
2a(a + b)

a0
a1
a2
a3

:=
:=
:=
:=

a4

:= a2

GEORGE BOROS AND VICTOR H. MOLL

Then
(2.10)

h(x)

and thus

tan1

k=1

2ax + a + b
a4 x4 + a3 x3 + a2 x2 + a1 x + a0

2ak + a + b
a4 k 4 + a3 k 3 + a2 k 2 + a1 k + a0

tan1 (a + b + c).
2

Special cases: b = a, c = a/2 yields

tan1

k=1

8ak
4a2 k 4 + (a2 + 4)

a
tan1 .
2
2

The particular case a = 1, b = 1 and c = 1/2 gives

(2.11)

tan1

k=1

8k
4k 4 + 5

1
tan1 .
2
2

b = a, c = 0 yields the sum

(2.12)

tan1

k=1

a2 k 4

2ak
a2 k 2 + 1

,
2

which is independent of a.
Additional examples can be given by telescoping twice (or even more).
Corollary 2.2. Let f and h be related by
h(x)

(2.13)
Then
n
X

tan1 h(k)

f (x + 1) f (x 1)
.
1 + f (x + 1)f (x 1)

tan1 f (n + 1) tan1 f (1) + tan1 f (n) tan1 f (0).

k=1

In particular,

(2.14)

tan1 h(k)

= 2 tan1 f () tan1 f (1) tan1 f (0).

k=1

Proof. The relation (2.13) shows that


tan1 h(k)

tan1 h(k)

tan1 f (k + 1) tan1 f (k 1).

Thus
n
X

k=1

=
=

n
X
 1

tan f (k + 1) tan1 f (k 1)

k=1

n
n
X
 1
 X
 1

tan f (k + 1) tan1 f (k) +
tan f (k) tan1 f (k 1)

k=1
1

tan

k=1

f (n + 1) tan1 f (1) + tan1 f (n) tan1 f (0).

Example 2.3. The evaluation

X
2
(2.15)
tan1 2
k

3
4

k=1

corresponds to f (k) = k so that h(k) = 2/k 2 . This is the problem proposed by


Anglesio [1].
Example 2.4. Take f (k) = 2/k 2 so that h(k) = 8k/(k 4 2k 2 + 5). It follows
that

X
1
8k
= tan1 .
tan1 4
k 2k 2 + 5
2
k=1

This sum is part b) of the Problem proposed in [1].

Example 2.5. Take f (k) = a/(k 2 + 1). Then h(k) = 4ak/(k 4 + a2 + 4), so that

X
4ak
a
(2.16)
tan1 4
= tan1 + tan1 a.
k + a2 + 4
2
k=1

Special cases: a = 1 yields

X
(2.17)
tan1
k=1

a=

4k
+5

k4

2 gives

(2.18)

tan

k=1

1
+ tan1 .
4
2

4 2k
k4 + 6

.
2

Differentiating (2.16) with respect to a gives

X
4k(k 4 + 4 a2 )
8
2
k + 2(a + 4)k 4 + 16a2 k 2 + (a4 + 8a2 + 16)

k=1

(a2

3(a2 + 2)
.
+ 1)(a2 + 4)

The special case a = 0 yields

(2.19)

k=1

k
k4 + 4

3
8

and a = 2 gives
(2.20)

k=1

k5
k 8 + 16k 4 + 64k 2 + 64

9
.
80

Mathematica evaluates the first sum but not the second.

The examples described above are rather artficial. The interesting question is
to find f (x) given the function h. In general it is not possible to find f in closed
form. In the case of Example 2.3, we need to solve the functional equation
(2.21)

2 [1 + f (x 1)f (x + 1)] = x2 [f (x + 1) f (x 1)] .

A polynomial solution of (2.21) must have degree at most 2 and trying f (x) =
ax2 + bx + c yields f (x) = x.

GEORGE BOROS AND VICTOR H. MOLL

3. The method of zeros


A different technique for the evaluation of arctangent sums is based on the factorization of the product
(3.1)

pn

n
Y

:=

(ak + ibk )

k=1

with ak , bk R. The argument of pn is given by


Arg(pn )

n
X

tan1

k=1

bk
.
ak

Example 3.1. Let


(3.2)

pn (z)

n
Y

(z zk )

k=1

be a polynomial with real coefficients. Then


(3.3)

Arg(pn (z))

n
X

tan1

k=1

x xk
.
y yk

The special case pn (z) = z 1 has roots at zk = cos(2k/n) + i sin(2k/n), so we


obtain
n
X
x cos(2k/n)
Arg(z n 1) =
tan1
(3.4)
.
y sin(2k/n)
k=1

Example 3.2. The classical factorization


(3.5)

sin z

= z


Y

k=1

z2
k2

yields the evaluation


(3.6)

tan1

k=1

2xy
k 2 x2 + y 2

= tan1

y
tanh y
tan1
.
x
tan x

Special cases: x = y yields

(3.7)

tan1

k=1

2x2
k2

x = y = 1/ 2 gives
(3.8)

tan1

k=1

1
k2

tanh x
tan1
.
4
tan x

tanh (/ 2)
,
tan1
4
tan(/ 2)

which corresponds to (1.3).


x = y = 1/2 yields
(3.9)

k=1

tan1

1
2k 2

.
4

Differentiating (3.7) gives

X
k2
(3.10)
4
k + 4x4

sin 2x sinh 2x
.
4x cos 2x cosh 2x

k=1

In particular, x = 1 yields

(3.11)

k=1

k2
+4

coth .
4

k4

The identity (3.10) is comparable to Ramanujans evaluation

X
k2

sinh x 3 3 sin x

(3.12)
=
k 4 + x2 k 2 + x4
2x 3 cosh x 3 cos x
k=1

discussed in [3], Entry 4 of Chapter 14.


Glasser and Klamkin [10] present other examples of this technique.
4. A functional equation
The table of sums and integrals [11] contains a small number of examples of
finite sums that involve trigonometric functions of multiple angles. In Section 1.36
we find
n
X
x
x
(4.1)
22k sin4 k = 22n sin2 n sin2 x
2
2
k=1
n
X

(4.2)

k=1

x
1
sec2 k
2k
2
2

cosec2 x

1
x
cosec2 n
2n
2
2

and Section 1.37 consists entirely of the two sums


n
X
1
x
1
x
(4.3)
tan k =
cot n 2 cot 2x
2k
2
2n
2
k=0

(4.4)

n
X
1
x
tan2 k
22k
2

k=0

22n+2 1
1
x
+ 4 cot2 2x 2n cot2 n .
3 22n1
2
2

In this section we present a systemtatic procedure to analyze these sums.


Theorem 4.1. Let
(4.5)

F (x) =

f (x, k)

and

G(x) =

k=1

(1)k f (x, k).

k=1

Suppose f (x, 2k) = f ((x), k) for some R and a function : R R. Then


(4.6)

F (x)

(2) F (

(n)

(x))

n1
X

(2)j G((j) (x)).

j=0

Proof. Observe that


F (x) + G(x) = 2

f (x, 2k) = 2

k=1

Repeat this argument to obtain the result.

k=1

f ((x), k) = 2F ((x)).

GEORGE BOROS AND VICTOR H. MOLL

Example 4.1. Let f (x, k) = 1/(x2 + k 2 ), so that = 1/4 and (x) = x/2. Since
F (x) =

k=1

x2

1
x coth x 1
=
2
+k
2x2

and

X
(1)k
x csch x 1
G(x) =
=
,
x2 + k 2
2x2
k=1

(4.6) yields, upon letting n ,

(4.7)

j=0

x
2j
sinh 2j x

x
.
tanh x

Now replace x by ln t, differentiate with respect to t, and set t = e to produce

X
2j coth 2j
2j sinh 2j
j=0

(4.8)

1 + 4e2 e4
.
1 2e2 + e4

Now go back to (4.7), replace x by ln t, differentiate with respect to t, set t = ae,


differentiate with respect to a, and set a = e to produce
(4.9)

X
2 22j + csch2 2j sech2 2j
22j sinh21j
j=0

e12 17e8 17e4 + 1


.
e12 3e8 + 3e4 1

Corollary 4.2. Let


(4.10)

F (x) =

x
X
f
k

and

G(x) =

k=1

(1)k f

k=1

x
k

Then, for any n N,


(4.11)

F (x)

= 2n F (2n x) +

n
X

2k G(2k x).

k=1

In particular, if F is bounded, then


(4.12)

F (x)

2k G(2k x).

k=1

Proof. The function f (x/k) satisfies the conditions of Theorem 4.1 with = 1 and
(x) = x/2. Thus
F (x) = 2n F (x/2n )

n1
X

2j G(x/2j ).

j=1

Now replace x by x/2 to obtain (4.11). Finally let n to obtain (4.12).


The key to the proof of Theorem 4.1 is the identity F (x) + G(x) = 2F ((x)).
We now present an extension of this result.

Theorem 4.3. Let F, G be functions that satisfy


(4.13)

F (x)

= r1 F (m1 x) + r2 G(m2 x)

for some parameters r1 , r2 , m1 , m2 . Then


(4.14)

r2

n
X

r1k1 G(mk1
m2 x) = F (x) r1n F (mn1 x).
1

k=1

Proof. Replace x by m1 x in (4.13) to produce


F (m1 x)

= r1 F (m21 x) + r2 G(m2 m1 x),

which, when combined with (4.13), gives


F (x)

= r12 F (m21 x) + r1 r2 G(m1 m2 x) + r2 G(m2 x).

Formula (4.14) follows by induction.


We now present two examples that illustrate Theorem 4.3. These sums appear
as entries in Ramanujans Notebooks.
Example 4.2. The identity
(4.15)

cot x =

1
x 1
x
cot tan
2
2 2
2

shows that F (x) = cot x, G(x) = tan x satisfy (4.13) with r1 = 1/2, r2 = 1/2 and
m1 = m2 = 1/2. We conclude that
(4.16)

n
X

2k tan

k=1

x
2k

1
x
cot n cot x.
2n
2

This is (4.3). It also appears as Entry 24, p. 364, of Ramanujans Third Notebook
as described in Berndt [4], p. 396. Similarly, the identity
(4.17)

sin2 (2x) =

4 sin2 x 4 sin4 x

yields (4.1). The reader is invited to produce proofs of (4.2) and (4.4) in the style
presented here.

Example 4.3. The identity


cot x =

(4.18)

cot

x
csc x
2

satisfies (4.13) with F (x) = cot x, G(x) = csc x and parameters r1 = 1, r2 =


1, m1 = 1/2, m2 = 1. We obtain
(4.19)

n
X

k=1

csc

x
2k1

cot

x
cot x.
2n

This appears in the proof of Entry 27 of Ramanujans Third Notebook in Berndt


[4], p. 398.

10

GEORGE BOROS AND VICTOR H. MOLL

Example 4.4. The application of Theorem 4.1, or Corollary 4.2, requires an analytic expression for F and G. A source of such expressions is Jolley [12]. Indeed,
entries 578 and 579 are

tan1

2x2
k2

(1)k1 tan1

2x2
k2

(4.20)

k=1

(4.21)

k=1

tanh x
tan1
4
tan x

sinh x
+ tan1
.
4
sin x

These results also appear in [5], page 314. Applying one step of Proposition 4.2 we
conclude that
tanh x
tanh 2x
sinh 2x
(4.22)
2 tan1
= tan1
+ tan1
.
tan x
tan 2x
sin 2x
We also obtain
n
n
X
sinh 2k x
1 tanh x
n
1 tanh 2 x
(4.23)
2k tan1
=
tan
,

2
tan
sin 2k x
tan x
tan 2n x
k=1

and by the boundedness of tan1 x conclude that

X
sinh 2k x
tanh x
(4.24)
= tan1
.
2k tan1
k
sin 2 x
tan x
k=1

Differentiating (4.23) gives


2

n
X
cos 2k x sinh 2k x cosh 2k x sin 2k x

k=1

cos 2k+1 x cosh 2k+1 x

sin 2x sinh 2x
sin 2n+1 x sinh 2n+1 x
+
.
cos 2x cosh 2x cos 2n+1 x cosh 2n+1 x
Letting n and using the identity
=

(4.25)


cos 2k+1 x cosh 2k+1 x = 2 sin2 2k x + sinh2 2k x

yields

X
cosh 2k x sin 2k x sinh 2k x cos 2k x
k=1

sin2 2k x + sinh2 2k x

sech2 x tan x tanh x sec2 x


+ sign x.
tan2 x + tanh2 x

For example, x = gives


(4.26)

csch 2k

coth 1.

k=1

5. Reduction to telescoping
The sum
(5.1)

S(f )

n
X

f (k, t),

k=1

depending on the parameter t, is said to telescope if the summand can be written


in the form
(5.2)

f (k, t) = f1 (k, t) f1 (k + m, t)

11

for a function f1 and m Z fixed. In this section we discuss a method to determine


if the sum S telescopes.
We first consider the case of a function f (k, t) that is rational in k. Then the
question of telescoping is decided by examining the partial fraction decomposition
of f . For simplicity, we assume that the poles of f are simple and we omit the
parameter t.
Proposition 5.1. Let
f (k)

(5.3)

r
X

j=1

aj
k kj

be the partial fraction decomposition of f . Then S(f ) telescopes if and only if f


can be written as

s 
X
bj
bj
(5.4)
f (k) =

k kj
k kj mj
j=1
where mj Z.
We now observe that if (5.1) telescopes, then so do the sums
n
X

f (k, t)
k

(5.5)

and

k=1

n
X

f (k, t).
t

k=1

In particular, the question of telescoping of the arctangent sum


n
X
(5.6)
tan1 R(k)
S(n) =
k=1

for a rational function R is reduced to that of the rational sum


n
X
1
R
(5.7)
S1 (n) =
,
1 + R2 (k) k
k=1

by differentiating with respect to k. For instance, the sum in


rational function with poles at
p
p
p
1
1
1
(1 1 4i/a), (1 + 1 4i/a), (1 1 + 4i/a),
2
2
2
and these can be paired as required in Proposition 5.1.

(2.12) produces a
p
1
(1 + 1 + 4i/a),
2

Example 5.1. Consider the sum




X
2k 1
2k 2 2k + 1
2
1
S =
k tan1 4

(k
+
1)tan
.
k 2k 3 + k 2 1
k 4 2k 3 + k 2 + 1
k=1

To evaluate S we introduce
2k 2 2k + 1
2k 1
A(k) = k tan1 4
(k 2 + 1)tan1 4
3
2
k 2k + k 1
k 2k 3 + k 2 + 1
and observe that
d3
(5.8)
A(k) = B(k) B(k 1),
dk 3
where
6
8(3k 3 5k 8) 64(k 3 k 1)
(5.9)
B(k) = 4

+
.
k +1
(k 4 + 1)2
(k 4 + 1)3

12

GEORGE BOROS AND VICTOR H. MOLL

Let C(k) be the function obtained by integrating B(k) three times:


(5.10)

C(k)

= (k 2 + k + 1)tan1 k 2 + P2 (k)

where P2 (k) is a polynomial of degree 2.


Integrating backwards we obtain

N 
X
2k 2 2k + 1
2k 1
1
2
1
k tan
(k + 1) tan
k 4 2k 3 + k 2 1
k 4 2k 3 + k 2 + 1
k=2

= C(N ) C(1)
= (N 2 + N + 1)tan1 N 2 + Q2 (N ),
where Q2 (N ) = P2 (N ) C(1) is another polynomial of degree 2.We have started
the sum at k = 2 because k 4 2k 3 + k 2 1 has a zero at k = 12 ( 5 + 1) 1.618.
The polynomial Q2 (N ) = aN 2 + bN + c can be determined from
aN 2 + bN + c =

(5.11)

N
X

A(k) + (N 2 + N + 1)tan1 N 2

k=2

by evaluating (5.11) at three distinct values of N . The result is




(5.12)
Q2 (N ) =
2N 2 + 2N 1 .
4
Thus
N 
X
k tan1

k=2

2k 2 2k + 1
2k 1
(k 2 + 1) tan1 4
4
k 2k 3 + k 2 1
k 2k 3 + k 2 + 1

= (N 2 + N + 1)tan1 N 2 +
so that

X
k tan1
k=1

(2N 2 + 2N 1),
4


2k 2 2k + 1
2k 1
3
2
1
(k + 1) tan
=1
.
4
3
2
4
3
2
k 2k + k 1
k 2k + k + 1
2

Note. Naturally this idea applies to a more general class of sums. For instance,
sums of the form
(5.13)

L(n)

n
X

p(k) ln R(k)

k=1

and
(5.14)

A(n) =

n
X

p(k) tan1 R(k),

k=1

for a polynomial p, can be reduced to a sum with rational summand by succesive


differentiation.

13

6. A dynamical system
In this section we describe a dynamical system that appears in the evaluation of
arctangent sums. Define
n
n
X
X
1
tan1 .
tan1 k and yn = tan
xn = tan
k
k=1

k=1

Then x1 = y1 = 1 and
xn =

nyn1 + 1
xn1 + n
and yn =
.
1 nxn1
n yn1

Proposition 6.1. Let n N. Then


(
yn
(6.1)
xn =
1/yn

if n is even
if n is odd

that is
(6.2)

tan

n
X

tan1 k

= tan

k=1

n
X

tan1

k=1

1
k

if n is even and
(6.3)

tan

n
X

tan1 k

cotg

k=1

n
X

tan1

k=1

1
k

if n is odd.
Proof. The recurrence formulas for xn and yn can be used to prove the result
directly. A pure trigonometric proof is presented next. If n is even then
tan

2m
X

k=1

tan1 k + tan

2m
X

k=1

tan1

1
k

tan

2m
X

tan1 k + tan

k=1

tan

2m
X

/2 tan1 k

k=1
1

tan

k=1

2m
X

k + tan m

2m
X

tan

k=1

0.

A similar argument holds for n odd.


This dynamical system suggests many interesting questions. We conclude by
proposing one of them: Observe that x3 = 0. Does this ever happen again?
References
[1] ANGLESIO, J.: Elementary problem 10292. Amer. Math. Monthly 100, 1993, 291. Solution
by several authors Amer. Math. Monthly, 103, 270-272.
[2] BERNDT, B.C.: Ramanujans Notebooks, Part I. Springer-Verlag, New York, 1985.
[3] BERNDT, B.C.: Ramanujans Notebooks, Part II. Springer-Verlag, New York, 1989.
[4] BERNDT, B.C.: Ramanujans Notebooks, Part IV. Springer-Verlag, New York, 1994.
[5] BROMWICH, T.J.: An introduction to the theory of infinite series. 1926.
[6] CHAPMAN, R.J.: Elementary problem 3375. Amer. Math. Monthly 97, 1990, 239-240.
[7] CHRYSTAL, G.: Algebra, Part II, 2nd. ed., A. and C. Black, London, 1922, p. 357.
[8] DARLING, D.: Telescoping series of arctangents. Amer. Math. Monthly 103, 1996, 270-272.
[9] GLAISHER, J.W.L.: A theorem in trigonometry, Quart. J. Math. 15, 1878, 151-157.
[10] GLASSER, M.L. - KLAMKIN, M.S.: On some inverse tangent summations. Fibonacci Quarterly, 14, 1976, 385-388.

14

GEORGE BOROS AND VICTOR H. MOLL

[11] GRADSHTEYN, I.S. - RYZHIK, I.M.: Table of Integrals, Series and Products. Sixth Edition,
ed. Alan Jeffrey, assoc. ed. D. Zwillinger. Academic Press, 2000.
[12] JOLLEY, L.B.W.: Summation of series, 1961
[13] LONEY, S.L.: Plane Trigonometry, Part II, Cambridge University Press, Cambridge, 1893,
p. 206.
[14] MILLER, A. - SRIVASTAVA, H.M.: On Glaishers infinite sums involving the inverse tangent function. Fibonacci Quart., 1992, 290-294.
[15] SARKAR, A.: The sum of arctangents of reciprocal squares. Amer. Math. Monthly, 98, 1990,
652-653.
[16] SCHAUMBERGER, N.: An old arctangent series reappears. The College Math. J. Problem
399. May 1990, vol. 21, 253-254.
Department of Mathematics, Xavier University, New Orleans, LA 70125
E-mail address: gboros@xula.edu
Department of Mathematics, Tulane University, New Orleans, LA 70118
E-mail address: vhm@math.tulane.edu